Global Notarial Digitalization - Aghenitei, Mihaela (Acta Universitatis Danubius. Juridica, 2022)
Digitization is one of the priorities of these times, because it solves many problems with minimal cost, as we all know and understand, both at the individual and institutional level. However, the pace and method adopted must consider many factors, not just the desire to develop at the pace of technology. The context is clear: the European institutions aim and even succeed in accelerating the digitization of justice to the highest level, imposing a creative point of view, and Artificial intelligence has already become conscious, which is wonderful, and it will not be long until the result artificial intelligence will arrive before us at home and at work. This article aims to briefly present the European trends in this matter, especially the steps taken by notaries in France and Romania in this direction, but also to support some reasons why we believe that now, more than ever, it is very important to hurry slowly.